Extending web applications to mobile platforms: a software engineering view - Peskersoy, Can; Tanintara-Art, Maleekanya (My University, 2013)
4 Abstract The purpose of this master thesis is to investigate the problems and solutions for a company who wants to expand their applications onto mobiles. It is important for the company if they can find the faster way to develop the same system onto mobile apps, what artifacts can be used in common and what can be reused. Even smartphones have ability to work almost like PC but they also have many limitations such as screen size, limited resources like RAM, disk, and battery. How can we compromise the full data context with those limitations? In this master thesis, we have studied all perspectives in the software engineering area and come up with problems and solutions through the real implementation of mobile apps. We have learned that a project plan and organization involvement at the beginning is crucial because the decision on the target market, software architecture, offline/ online necessity affects a lot later on in the implementation phase. We have found out that a large extent on the reuse is based on the software architecture and design pattern. The tradeoff between using the same design pattern and different mobile frameworks’ best fits design patterns is a one interesting future study topic. A testing coverage is also one topic that we have found out needed because a mobile app needs more considerations than a traditional application.
Keywords: Data- och informationsvetenskap; Computer and Information Science